EFEKTIVITAS IMPLEMENTASI SISTEM ABSENSI FINGER PRINT (SIDIK JARI) DALAM MENINGKATKAN DISIPLIN KERJA KARYAWAN (Studi Pada Haul Truck Maintenance Departement PT. Kaltim Prima Coal) - Erni, Erni (PREDIKSI, 2016)
This study aims to determine how far the effectiveness of the implementation of fingerprint attendance system, to determine the level of discipline of employees and to determine the effectiveness of the implementation of fingerprint attendance system in improving employee discipline.The results showed that the results of empirical rs amounted to 0.964 greater than the theoretical rs amounted to 0,139. The results of these calculations lies in the interval from 0.80 to 0.100, which means that there is a strong and significant correlation between the variables fingerprints with variable work discipline.The results also showed that the t-test results are t-empirical (50.878) is greater than the t-theoretical (1,972), this means that there are significant and significant relationship between the variables fingerprints with variable work discipline. Thus it can be said that the hypothesis that the writer formulated in this study can be received and verified.